Co-delivery of oxygen and erlotinib by aptamer-modified liposomal complexes to reverse hypoxia-induced drug resistance in lung cancer. (November 2017) - Li, Fengqiao; Mei, Hao; Gao, Yu; Xie, Xiaodong; Nie, Huifang; Li, Tao; Zhang, Huijuan; Jia, Lee
Abstract: Tumor hypoxia is a common feature of the tumor microenvironment and has been regarded as one of the key factors in driving the emergence of drug resistance in solid tumors. To surmount the hypoxia-associated drug resistance, we fabricated the novel multifunctional liposomal complexes (ACLEP) that could co-deliver oxygen and molecular targeted drug to overcome the hypoxia-induced drug resistance in lung cancer. The ACLEP were fabricated with liposomes anchored with anti -EGFR aptamer-conjugated chitosan to co-administrate erlotinib and PFOB to EGFR-overexpressing non-small-cell lung cancer. Our results showed that the ACLEP possessed desired physicochemistry, good biostability and controlled drug release. The entrapped PFOB in nanoparticle facilitated the uptake of ACLEP in either normoxia or hypoxic condition. Comparing to those nanoparticles loading erlotinib alone, our innovative oxygen/therapeutic co-delivery system showed a promising outcome in fighting against hypoxia-evoked erotinib resistance both in vitro and in vivo . Hence, this work presents a potent drug delivery platform to overcome hypoxia-induced chemotherapy resistance. Graphical abstract: